Irish Existentials in Context. (December 2014) - McCloskey, James
Abstract This paper aims to contribute to the comparative typology of existential constructions by examining Irish existentials in detail. It goes on to engage some of the central theoretical issues raised in that investigation and provides support for the bifurcated analysis of the definiteness restriction proposed by McNally (1992). It identifies what is argued to be a true existential predicate and argues that there is no common syntactic form for existentials crosslinguistically; rather, the observed commonalities among existentials across languages reflect semantic primitives out of which they are constructed. Diversity in the expression of existential propositions principally reflects different patterns of lexicalization.